Personalized Learning Environment (PLE): Developing A Framework Using ADDIE Approach - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Che Pee @ Che Hanapi, Ahmad Naim (AENSI Journals, 2014)
Background: This paper is a review on Personalized Learning Environments (PLE) focusing on framework development. PLE are portable, ubiquitous learning spaces that allow students to learn to learn, connect with multidisciplinary viewpoints, engage in critical and creative practices, and nurture and develop their learning identity. Personalization is seen as the key approach to handle the plethora of information in today’s knowledge-based society. It is expected that personalized teaching and learning will address the needs of the learners more efficiently. Objective: The objective of this study is to develop learning framework based on the proposed model for students using PLE approach. Results: Additionally, the difference between PLE and traditional method is also presented for incorporating PLEs into a classroom. In this paper, a systematic research framework using ADDIE (Analyze, Design, Develop, Implement and Evaluate) approach is proposed for Personalized Learning Environment (PLE). Conclusion: Overall, this paper discuss the proposed of PLE framework to replace restrictive learning systems.